Hearing status of the elderly in nursing homes in Galicia: pilot study - Vázquez Sánchez, María Covadonga; del Oro Sáez, Carlos Pio; Seoane, Santiago; Gigirey Prieto, Luz María (Auditio, 2021)
Various studies show the close relationship between aging and decreased hearing sensitivity. Galicia occupies the third place in the ranking of Spanish regions with the highest percentage (21.6%) of elderly people (65 or over) and is the autonomous community that loses population more quickly. At the same time, in our community there is a high percentage of elderly people who report hearing problems (INEBase, 2010). However, despite this statistical evidence, no audiological study has been performed to date. Objective: To establish, through a pilot screening program developed in Galician Centers for the Third Age, the audiological bases that allow characterizing the hearing status of the elderly Galician population. Method: We evaluated 402 subjects (≥ 60 years). The audiological protocol consisted of an otoscopy, followed by a Liminar Tonal Audiometry and the Whisper Test. The diagnosis of hearing damage was made based on the international criteria of Ventry and Weinstein. Results: 58% of the residents presented hearing loss, its prevalence being higher in men (63.9% versus 54.7%). We found significant differences in the mean thresholds (p <0.05) and in the HFPTA (1-4KHz) (p <0.05) between genders, as well as in terms of age. Conclusion: Considering the demographic change experienced by Galician society, our results place hearing loss among the main public health problems of the future.